117 Sustained and rapid B-cell depletion with ofatumumab: population pharma- cokinetic B-cell modeling in relapsing MS patients. Issue 6 (27th May 2022) - Graham, Gordon; Kahn, Joseph; Savelieva, Marina; Yu, Huixin; Pingili, Ratnakar; Willi, Roman; Ramanathan, Krishnan; David, Olivier; Häring, Dieter; Bagger, Morten
Abstract : Objectives: To characterize the pharmacokinetic (PK) relationship of ofatumumab for B-cell counts in RMS patients, assess the PK and B-cell dynamics given the Phase 3 dose regimen through PK-B-cell simulations and explore the effect of covariates on PK and B-cells. Methods: The PK-B-cell model was developed using data from Phase 2 and 3 trials. Simultaneous fitting was performed to assess the interaction between PK and B-cells. Effect of body weight, age, administra- tion route, s.c. injection device, and baseline B-cell count on PK and B-cell parameters were evaluated. Results: In total, 9, 168 plasma concentrations from 1, 440 patients were included in PK analysis and 17, 158 B-cell counts from 1, 486 patients in B-cell analysis. Simulations demonstrated a rapid, median B-cell depletion to <10 cells/µL in 8.75 days; no signs of B-cell repletion occurred between doses, and >94% of patients had <10 cells/µL at B-cell steady state and pre-dose. Regardless of weight, all patients achieved low B-cell counts, similar to results observed in Phase 3 trials. Baseline age, B-cell counts and injection device had negligible effect on PK parameters. Conclusion: The PK-B-cell model showed early, rapid, and sustained B-cell depletion with ofatumumab, confirming the rationale for the chosen Phase 3 dosing regimen. Funding statement.This study was funded by Novartis Pharma AG, Basel, Switzerland. teresa.sawtell@novartis.com